2019
DOI: 10.3758/s13421-019-00977-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of state change on object representations in language comprehension

Abstract: To understand language people form mental representations of described situations. Linguistic cues are known to influence these representations. In the present study, participants were asked to verify whether the object presented in a picture was mentioned in the preceding words. Crucially, the picture either showed an intact original state or a modified state of an object. Our results showed that the end state of the target object influenced verification responses. When no linguistic context was provided, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 49 publications
6
35
2
Order By: Relevance
“…"weigh"). Using the picture verification paradigm, Kang, Eerland, Joergensen, Zwaan, & Altmann (2019) found that participants reacted faster to a target probe object (e.g. a dropped ice cream cone) when it matched the end state of the event ("The woman will drop the ice cream") than when it (most likely) did not ("The woman will choose the ice cream").…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…"weigh"). Using the picture verification paradigm, Kang, Eerland, Joergensen, Zwaan, & Altmann (2019) found that participants reacted faster to a target probe object (e.g. a dropped ice cream cone) when it matched the end state of the event ("The woman will drop the ice cream") than when it (most likely) did not ("The woman will choose the ice cream").…”
Section: Methodsmentioning
confidence: 99%
“…However, they might also, or instead, retrieve the object representation that matches the most probable end state as described in linguistic context (e.g. more looks at the intact state when a minimal change of state is described, and more looks at the chopped state when a substantial change is described), as might be predicted by Kang et al (2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual attention, a core cognitive process that is vital for our survival, is welldocumented to be modulated by the language. Upon hearing or reading an object name or an event, we activate implied perceptual properties of the target object such as its state (Kang et al, 2019), orientation (Stanfield & Zwaan, 2001), shape (Zwaan, Stanfield, & Yaxley, 2002), visibility (Yaxley & Zwaan, 2007), color (Hoeben-Mannaert , Dijkstra, & Zwaan, 2017;; Richter & Zwaan, 2009), and location and motion direction (Bergen, Lindsay, Matlock, & Narayanan, 2007;; Chasteen, Burdzy, & Pratt, 2010;; Dudschig, Souman, Lachmair, Vega, & Kaup, 2013;; Estes, Verges, & Adelman, 2015;; Estes, Verges, Barsalou, 2008;; Gozli, Chasteen, & Pratt, 2013;; Richardson, Spivey, Barsalou, & McRae, 2003;; Šetić & Domijan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We predict that participants would establish multiple conflicting object-state representations during sentence comprehension and cognitive resources are required to resolve this ambiguity. During the first sentence, participants may establish the described mental representations of the target object and may pay more attention to the item when it matches than mismatches the described object representation (Kang et al, 2019(Kang et al, , 2020. During the second sentence, participants may update the mental representation of the target object by suppressing or discarding the irrelevant ones (Hindy, Kalenik, & Thompson-Schill, 2012;; Solomon, Hindy, Altmann, & Thompson-Schill, 2015).…”
Section: Introductionmentioning
confidence: 99%